Gender disparities in knowledge of urban adolescents dating violence: differential item function analysis in rasch model - Ayu, Suci Musvita; Sofiana, Liena; Wardani, Yuniar; Gustina, Erni; Sukarelawan, Moh. Irma (International Journal of Public Health Science (IJPHS), 2025)
Adolescent dating violence (ADV) is a global public health problem that has a serious impact on adolescents' physical, psychological, and social development. This study aimed to explore gender disparities in Indonesian adolescents' knowledge of dating violence using the Rasch Model and Differential Item Function Analysis. A total of 250 junior high school students in Yogyakarta, consisting of 107 males and 143 females, participated. The ADV knowledge measurement instrument consisted of 16 previously tested items for validity and reliability. Results showed that female students had a higher level of knowledge than male students, especially in identifying emotional and physical violence. Differential item function (DIF) analysis revealed that two items showed differences in perception based on gender, with female students focusing more on physical violence. In contrast, male students tended to view physical violence as a more common behaviour. This study highlights the importance of more inclusive and gender-sensitive educational programs to increase adolescents' knowledge of different forms of dating violence. The findings provide important insights for the development of interventions that can help prevent dating violence among adolescents.